PEMANFAATAN APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK ANALISIS POTENSI EROSI DAS SILAT - Willianto, Hengky; Herawati, Henny; Kartini, Kartini (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2023)
Silat watershed located in Silat Hulu and Silat Hilir Districts in Kapuas Hulu Regency. As a rainwater catchment area, Silat Watershed has erosion and sedimentation problems. This research conducted to formulate factors that cause erosion to calculate erosion rate and determine class and level of erosion hazard. The study used USLE method by utilizing ArcGIS software to help determine class and level of erosion hazard. Factors that determine erosion include erosivity, erodibility, topography, and vegetation. Silat watershed has an area of 142725.9 hectares. Erosion hazard level is divided into 5 classes. Total erosion in 2000 reached up to 7,174,094.7 tonnes/year with very light erosion concists 49.03% area, light erosion concists 5.04% area, moderate erosion concists 38.07% area, heavy erosion concists 7.74% area. very heavy erosion 0.11% area. Total erosion in 2011 reached 8,045,591.3 tonnes/year with very light erosion concists 45.91% area, light erosion concists 4.92% area, moderate erosion concists 39.27% area, heavy erosion concists 9.73% area. very heavy erosion 0.17% area. Total erosion in 2019 reached up to 9,177,089.694 tonnes/year with very light erosion concists 43.07% area, light erosion concists 4.63% area, moderate erosion concists 39.74% area, heavy erosion concists 12.29% area . very heavy erosion 0.27% area.